Nutritional strategies to influence adaptations to training - Spriet, L. L.; Gibala, M. J. (Journal of Sports Sciences, 2004)
This article highlights new nutritional concerns or practices that may influence the adaptation to training. The discussion is based on the assumption that the adaptation to repeated bouts of training occurs during recovery periods and that if one can train harder, the adaptation will be greater. The goal is to maximize with nutrition the recovery/adaptation that occurs in all rest periods, such that recovery before the next training session is complete. Four issues have been identified where recent scientific information will force sports nutritionists to embrace new issues and reassess old issues and, ultimately, alter the nutritional recommendations they give to athletes. These are: (1) caffeine ingestion; (2) creatine ingestion; (3) the use of intramuscular triacylglycerol (IMTG) as a fuel during exercise and the nutritional effects on IMTG repletion following exercise; and (4) the role nutrition may play in regulating the expression of genes during and after exercise training sessions. Recent findings suggest that low doses of caffeine exert significant ergogenic effects by directly affecting the central nervous system during exercise. Caffeine can cross the blood-brain barrier and antagonize the effects of adenosine, resulting in higher concentrations of stimulatory neurotransmitters. These new data strengthen the case for using low doses of caffeine during training. On the other hand, the data on the role that supplemental creatine ingestion plays in augmenting the increase in skeletal muscle mass and strength during resistance training remain equivocal. Some studies are able to demonstrate increases in muscle fibre size with creatine ingestion and some are not. The final two nutritional topics are new and have not progressed to the point that we can specifically identify strategies to enhance the adaptation to training. However, it is likely that nutritional strategies will be needed to replenish the IMTG that is used during endurance exercise. It is not presently clear whether the IMTG store is chronically reduced when engaging in daily sessions of endurance training or if this impacts negatively on the ability to train. It is also likely that the increased interest in gene and protein expression measurements will lead to nutritional strategies to optimize the adaptations that occur in skeletal muscle during and after exercise training sessions. Research in these areas in the coming years will lead to strategies designed to improve the adaptive response to training.